History of the Christian church ; v. III - Schaff, Philip, 1819-1893 (Grand Rapids, MI Eerdmans, 1910)
Contents : v. III : Nicene and Post Nicene Christianity from Constantine the Great to Gregory the Great A.D. 311-600
First published in 7 volumes, 1882-1892. 8 volume set
Keywords: Church history -- Early Church -- 311 - 600 A.D.